Knowledge and practice of informed consent by physiotherapists and therapy assistants in KwaZulu-Natal Province, South Africa - Kayode S. Aderibigbe; Sylvester C. Chima (AOSIS, 2019)
Background: Informed consent is a doctrinal prerequisite in accordance with the National Health Act 2003 and professional ethical guidelines. Current regulations stipulate that healthcare professionals obtain informed consent from patients prior to treatment. Misconduct charges relating to inadequate information disclosure have been recorded against South African physiotherapists. Objectives: This study evaluated knowledge and barriers to informed consent practice among physiotherapists and assistants at Ethekwini District public health institutions. Methods: This cross-sectional study utilised self-administered questionnaires. Statistical Package for Social Sciences was used to analyse variables. Significance level and attitude correlation was determined using chi-squared tests, Pearson's correlation and Spearman's coefficient. Results: Forty-nine respondents (43 physiotherapists, 3 technicians, 3 assistants) completed this study. Mean age and professional experience of respondents were 38 and 14 years, respectively. The majority were female (93%); 56% spent 5 to 10 min obtaining informed consent, mostly verbally (89%); while 47% correctly identified age of consent to routine treatment (12 years). Information provided to patients by respondents included treatment benefits (100%), common risks (81%) and 'all material risks' (31%). Fifty per cent of respondents showed positive attitudes to informed consent. Conclusions: Some practising physiotherapists and assistants in KwaZulu-Natal public healthcare institutions had only partial knowledge of informed consent regulations and local laws. Barriers to informed consent included language and excessive workload. Clinical implications: Patient-centred care is quality healthcare, and adequate informed consent knowledge improves clinical outcomes, respects patients' dignity and autonomy. Continued professional education on healthcare law and ethics should be provided to practising physiotherapists and assistants.